2016
DOI: 10.1016/j.scitotenv.2016.06.112
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the impact of uncertainty on the accuracy of large wildfire spread simulations

Abstract: Predicting wildfire spread is a challenging task fraught with uncertainties. 'Perfect' predictions are unfeasible since uncertainties will always be present. Improving fire spread predictions is important to reduce its negative environmental impacts. Here, we propose to understand, characterize, and quantify the impact of uncertainty in the accuracy of fire spread predictions for very large wildfires. We frame this work from the perspective of the major problems commonly faced by fire model users, namely the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…The capture of such variation necessitates a large number of sampling plots, resulting in trade-offs between the level of detail measured at a sampling unit and the number of sampling units that can be collected. To resolve this requires an understanding of the sensitivities of fire models to the relevant inputs (e.g., [89,90]), although ideally this would be driven by fundamental fire theory [91].…”
Section: Assessing Fuel Attributes In the Fieldmentioning
confidence: 99%
“…The capture of such variation necessitates a large number of sampling plots, resulting in trade-offs between the level of detail measured at a sampling unit and the number of sampling units that can be collected. To resolve this requires an understanding of the sensitivities of fire models to the relevant inputs (e.g., [89,90]), although ideally this would be driven by fundamental fire theory [91].…”
Section: Assessing Fuel Attributes In the Fieldmentioning
confidence: 99%
“…The impact of ignition location uncertainty has been shown to significantly affect simulated fire patterns [16]. Benali, et al [59] used satellite-derived ignitions to model fire growth and found that the uncertainty associated with ignition location had a large impact on the accuracy of simulations, while the impact of the uncertainty associated with ignition date/hour was relatively low.…”
Section: Potential and Limitations Of Satellite Datamentioning
confidence: 99%
“…Arca et al, 2007;Duguy et al, 2007;González-Olabarría et al, 2012;Jiménez et al, 2016;Oliveira et al, 2016;Madrigal et al, 2017). Nevertheless, crown fire models have not been tested by experimental burns in Mediterranean conditions and the predictions may therefore be misleading (Cruz & Alexander, 2010;Benali et al, 2016), leading to the application of inappropriate forest and fire management activities.…”
Section: Introductionmentioning
confidence: 99%